Model-Model Kepemimpinan Pendidikan Islam dalam Meningkatkan Mutu Lembaga Pendidikan - Istikhori Istikhori; Vera Siti Magfiroh; Ressy Resviati Putri; Lia Aliyah; Leni Sumarni; Amir Mirdad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Leadership is a strategic factor in improving the quality of Islamic educational institutions. The challenges of social change and globalization demand leadership models that are not only managerially effective but also grounded in Islamic values. This study aims to analyze models of Islamic educational leadership and their implications for institutional quality. The research method employed is a literature review, examining books and national and international journal articles indexed in Scopus and SINTA over the last five years. The findings indicate that transformational, visionary, democratic, and prophetic leadership play a significant role in enhancing educator performance, building an Islamic organizational culture, and strengthening the governance of Islamic educational institutions. The integration of Islamic values with modern leadership principles emerges as a strategic approach to developing the quality of Islamic education.